A graphical tuning method for fractional order controllers based on iso-slope phase curves. (October 2020) - Muñoz, Jorge; Monje, Concepción A.; Nagua, Luis F.; Balaguer, Carlos
Abstract: Fractional order controllers are widely used in the robust control field. As a generalization of the ubiquitous PID controllers, fractional order controllers are able to reach design specifications their integer counterparts cannot, and as a result they outperform them at particular situations. Their main drawback is that generalization of the design tools is not always evident, and therefore tuning this kind of controller is always a new and different challenge. Existing methods often use numerical computation to find the controller parameters that fit the specifications. This paper describes a graphical solution for fractional order controllers, which avoids the solution by nonlinear equations and helps designer to solve the control problem in a very intuitive way. This approach is tested in the servomotors of a real bio-inspired soft neck and results are compared with those obtained from other control strategies. The experiments show that the controller tuned by this method works as expected from a robust controller and that this approach is very competitive compared to other state of the art methods, while offering a more simplified and direct tuning process. Highlights: Robust control of a soft robotics platform. New Graphical method for fractional order controller tuning. Test and validation against state of the art methods. Experiments on a real soft robotics platform.